BIOGAS PRODUCTION FROM DAIRY CATTLE MANURE SUBJECTED TO CHEMICAL PRE-TREATMENT - Andrade, W.R.; Santos, T.M.B.; Arruda, L.D.O.; Rosa, E.M.; Cappi, N. (Revista Brasileira de Engenharia de Biossistemas, 2018)
Alkali and acid chemical pre-treatment for lignocellulosic biomass can affect the amount of energy harvested from it during the anaerobic digestion process. This study aimed to assess the biogas production of dairy cattle manure subjected to acid and alkaline pre-treatment. This assay was performed in two phases, which consisted of 10 days of pre-treatment and 120 days of anaerobic digestion. The substrates for pre-treatment and anaerobic digestion phase were calculated to attain 5% of total solids (TS). Pre-treatment phase was conducted during 10 days and the following experimental treatments were used: Control (Water); 2.5% of hydrochloric acid (HCl-2.5%), 2.5% of dolomite limestone (DI-2.5%), 5.0% of hydrochloric acid (HCl-5.0%) and 5.0% of dolomite limestone (DI-5.0%). After this phase, pH of all substrates had their values corrected to the start of the anaerobic digestion phase. Higher volatile solids reduction was attained by treatment Dl-5.0% whose biogas production and biogas yield per kg of waste was significantly higher compared to control treatment. Cattle manure pre-treated with 5.0% of dolomite limestone for 10 days incremented the biogas yield per kg of waste.